Reactive Pulmonary Capillary Hemangiomatosis and Pulmonary Veno-Occlusive Disease in a Patient with Repaired Scimitar Syndrome. (16th March 2016) - Güttinger, Eva; Vrugt, Bart; Speich, Rudolf; Ulrich, Silvia; Schwitz, Fabienne; Arrigo, Mattia; Huber, Lars C.
Abstract : Pulmonary capillary hemangiomatosis (PCH) is a rare histological substrate within the spectrum of pulmonary arterial hypertension that possibly represents an unusual manifestation of pulmonary veno-occlusive disease (PVOD). One of the histological hallmarks of PCH is the proliferation of pulmonary capillaries in the alveolar septa that infiltrate adjacent structures such as bronchioles, vessels, and visceral pleura. The hyperplastic process involving the smallest vessels of the pulmonary vascular bed might reflect uncontrolled angiogenesis, but whether this vascular proliferation is idiopathic or, conversely, a reactive process remains to be elucidated. Here we discuss the pathogenesis of PCH exemplified by the first reported case of a young patient with repaired scimitar syndrome that developed unilateral PCH.